ONLINE LEARNING: ENHANCING COMMUNICATIVE-BASED JAPANESE COMPETENCE THROUGH ZOOM AND AIZUCHI SKILL-BASED MULTIMEDIA - Imelda, Nuruddin, Rahmat Aceng (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Communicative-based Japanese Learning has been applied since the outbreak of the COVID-19 pandemic through Zoom and Aizuchi skill-based multimedia. This study aims to investigate the learners' initial attitude of learning communicative-based Japanese using Zoom and multimedia-based methods, the impact of online learning using Zoom and multimedia to learn Japanese, the participants' attitude towards multimedia that has characteristics, autonomous material, and media effectiveness, as well as the advantages and disadvantages of learning communicative-based Japanese using Zoom and Aizuchi skill-based multimedia. The descriptive analysis is used as the method in this study. The data collected were processed using the scale of Likert and Guttman. This research was conducted for six months in the Japanese Literature Study Program of the University of Hasanuddin Makassar. The research subjects were 30 middle students who have been learning Japanese for more than two years. The results of the study proved that communicative-based Japanese learning using Zoom and Multimedia for students is very positive ever since it began. The use of Zoom and Multimedia provides motivation, comforts, and learners' creativity, interaction with lecturers and colleagues, and good access to learning despite the COVID-19 pandemic. Nonetheless, the amount of cost required concerning the large internet quota needed, particularly during bad weather, is considered the biggest obstacle for learners.